Investigation of haloperoxidase properties extracted from Sargassum Binderi Sonder Ex J. Agardh (Sargassaceae, Fucales) / Thillai Punitha Segaran - Thillai Punitha , Segaran (2019)
Vanadium haloperoxidases (V-HPOs) are key enzymes that catalyze halides in the presence of hydrogen peroxide (H2O2) producing halogenated compounds. These HPOs have been characterized into vanadium chloroperoxidase (V-CPO), vanadium bromoperoxidase (V-BPO) and vanadium iodoperoxidase (V-IPO). Previous studies show that V-CPO and V-BPO have also been identified in eukaryotic species. In the present study haloperoxidase from a marine brown alga (seaweed) Sargassum binderi Sonder ex J. Agardh. was extracted and its properties were investigated. This brown seaweed collected from a fringing coral reef, at Cape Rachado, Port Dickson, west coast of Peninsular Malaysia produces HPO, that was extracted using two- phase aqueous system developed by Vilter (1994). The crude extract incubated with sodium metavanadate exhibits enhanced haloperoxidase activity, showing the presence of vanadium haloperoxidase. In addition the rate of activity was also increased by the addition of H2O2.The enzymatic activity was stabilized by introducing the optimized pH, buffer concentration and temperature. Substrate and enzyme concentration were used to determine the initial rates of reaction. Increased interest in these enzymes are a result of their increasing importance in the pharmaceutical industry.